Hydrogen reduction of spent lithium-ion battery cathode material for metal recovery: Mechanism and kinetics - Huang, Zhu; Yu, Dawei; Makuza, Brian; Tian, Qinghua; Guo, Xueyi; Zhang, Kun (Frontiers in Chemistry, 2022)
Hydrogen reduction is becoming a promising method for recycling lithium-ion battery cathode materials. However, the reaction mechanism and kinetics during hydrogen reduction are unclear, requiring further investigation. Therefore, non-isothermal and isothermal reduction experiments were conducted to evaluate the temperature dependence of the hydrogen reduction kinetics using simultaneous thermogravimetric and differential thermal analysis equipped with mass spectrometry. XRD and SEM were used to characterize the reduction products to understand the underlying reduction mechanisms. The hydrogen reduction profile could be divided into three main stages: decomposition of cathode materials, reduction of the resultant nickel and cobalt oxides, and reduction of LiMnO2 and residual nickel and cobalt oxides. The hydrogen reduction rate increased with increasing temperature, and 800°C was the optimum temperature for separating the magnetic Ni-Co alloy from the non-magnetic manganese oxide particles. The apparent activation energy for the isothermal tests in the range of 500–700°C was 84.86 kJ/mol, and the rate-controlling step was the inward diffusion of H2(g) within each particle. There was an downward progression of the reduction through the material bed for the isothermal tests in the range of 700–900°C, with an apparent activation energy of 51.82 kJ/mol.